Learning About Measurements from Videos of Keraton Kesepuhan Cirebon for Local Primary Students - Siti Kholisoh; Dafid Slamet Setiana (Ethnomathematics Journal, 2022)
Learning mathematics is sometimes monotonous and boring. For this reason, teachers are required to be able to create interesting and not boring learning media that can increase students' interest in learning mathematics. One of the learning media that can attract students' interest is making a video for learning mathematics to calculate distance units that are integrated with the local culture of the Kesepuhan Cirebon palace. With this learning video, it is hoped that students will be interested in participating in mathematics learning and getting to know the local culture, so that student learning achievements can increase. The research method used is the descriptive qualitative method. Data was collected using interview techniques, offline learning observations, and school documentation, data analysis was carried out using interactive analytical techniques consisting of three steps, namely data reduction, data presentation, and drawing conclusions. From the results of the study, it was found that the innovation of learning media videos to calculate distance units that were integrated with the local culture of the Kesepuhan Cirebon palace was able to increase student interest in learning and student achievement, this can be seen from the ability of students to convert distance units from places in the Kesepuhan palace, Cirebon.